A comprehensive review on surface post-treatments for freeform surfaces of bio-implants - Hashmi, Abdul Wahab; Mali, Harlal Singh; Meena, Anoj; Saxena, Kuldeep K.; Ahmad, Shadab; Agrawal, Manoj Kumar; Sagbas, Binnur; Valerga Puerta, Ana Pilar; Khan, Muhammad Ijaz (Journal of materials research and technology, 2023)
Surface finish is an essential factor in determining product sustainability and functionality. Most methods have been developed that can be utilized to manufacture optical, mechanical, and electrical devices with a micrometer or submicrometric precision, nanoscale surface roughness, and practically no surface flaws. Finishing technologies are classified into two types: those that use magnetic force and those that do not. These techniques provide flexible finishing tools that may be used efficiently for complicated freeform components. Due to limitations in finishing tool movement over the complex freeform geometry of the components, traditional finishing methods perform relatively badly when finishing sophisticated freeform surfaces. The life and function of the implant are determined by the surface conditions of biomedical components, such as heart valves, dental crowns, knee, elbow, and hip joints. Implants are often made of polymers, metals, ceramics, skin, bone, other human tissues, and other materials. Non-traditional finishing methods using loose abrasives offer greater finishing accuracy, uniformity, performance, and cost-effectiveness. Using abrasive-based finishing technologies like abrasive flow machining, magnetic abrasive finishing, magnetorheological fluid-based finishing, elastic emission machining, heat treatment, surface coating, and laser surface processing, etc., this article critically reviews the published research on fine finishing of freeform surfaces, i.e., biomedical implants, to improve their functionality and surface quality.